Signaling in dopamine D2 receptor-oxytocin receptor heterocomplexes and its relevance for the anxiolytic effects of dopamine and oxytocin interactions in the amygdala of the rat - de la Mora, Miguel Pérez; Pérez-Carrera, Diana; Crespo-Ramírez, Minerva; Tarakanov, Alexander; Fuxe, Kjell; Borroto-Escuela, Dasiel O. (Elsevier, 2016)
Dopamine D2 receptor (D2R)–oxytocin receptor (OTR) interactions exist within heterocomplexes with facilitatory effects on D2R recognition and Gi/o coupling. In this work the hypothesis is tested using cotransfected HEK293 cells whether allosteric reciprocal D2R-OTR interactions can enhance signaling of D2R-OTR heterocomplexes along the CREB, MAPK and PLC pathways and whether the anxiolytic effects of OT may involve facilitatory D2R-OTR interactions within the central amygdaloid nucleus (CeA). Oxytocin enhanced the D2-like agonist quinpirole induced inhibition of the AC-PKA-pCREB signaling cascade and increased its signaling over the RAS-MAPK-pELK pathway. Quinpirole enhanced the oxytocin induced increases in the activity of the PLCbeta-IP3-calcineurin and RAS-MAPK-pELK cascades. Bilateral infusion of oxytocin (0.9–150 ng/side) into the CeA of the rat elicited anxiolytic effects in the Shock-Probe Burying test, an unconditioned model of fear/anxiety. This action was not observed when oxytocin (25 ng/side) was simultaneously co-infused with raclopride (neither 250 nor 500 ng/side), a D2/D3 antagonist, into the CeA. Based on the current findings, the blockade of the anxiolytic effects of oxytocin by the simultaneous intra-CeA administration of raclopride can be explained by a lack of facilitatory protomer interactions in D2R-OTR heterocomplexes. Dysfunction and/or disruption of such interactions in the central amygdala may lead to anxiety development. Restoration of such interactions may represent a new strategy for development of novel anxiolytic drugs.
Keywords: Dopamina - Receptores; Receptores; Anxiety; Fear; Amygdala; Dopamine D2 receptor; Oxytocin receptor; Receptor-receptor interactions; Raclopride; Oxytocin; Heteroreceptor complexes